Effect of Potting Media on Seedling Growth and Quality Parameters of Prunus cerasoides D. Don seedlings under Nursery Conditions: RESEARCH PAPER - Pitamber Singh Negi; Anita Chauhan; Gopal Singh, Gopal Singh (Annals of Arid Zone, 2025)
A study was conducted to assess the impact of various potting media combinations on the seedling growth and quality parameters of Prunus cerasoides seedlings under nursery conditions. The seeds of Prunus cerasoides were sown in polybags filled with different potting media with seven treatments comprising various combinations of soil, sand and farmyard manure, and five replications in a completely randomized design to study their effect on seedling growth and quality parameters. Significant differences were observed in seedling growth parameters, shoot, root & total biomass, and quality parameters of Prunus cerasoides seedlings raised in different potting media in the nursery. The maximum growth of various seedling parameters viz., shoot length (101.50 cm), collar diameter (3.38 mm), root length (38.30 cm), number of roots (31.50), shoot fresh biomass (26.00 g seedlings-1), root fresh biomass (16.20 g seedlings-1), total fresh biomass (42.20 g seedlings-1), shoot dry biomass (14.00 g seedlings-1), root dry biomass (9.00 g seedlings-1) and total dry biomass (23.00 g seedlings-1) was recorded in seedlings raised in potting media composed of soil, sand, and farmyard manure (1:1:2) whereas minimum growth of various seedling growth parameters viz., shoot length (47.05 cm), collar diameter (1.29 mm), root length (22.30 cm), number of roots (21.20), shoot fresh biomass (2.33 g seedlings-1), root fresh biomass (1.33 g seedlings-1), total fresh biomass (3.66 g seedlings-1), shoot dry biomass (1.37 g seedlings-1), root dry biomass (0.67 g seedlings-1) and total dry biomass (2.04g seedlings-1) was recorded in seedlings raised in potting media composed of nursery soil only. Similarly, the maximum value of volume index (343.07cm2) and least value of sturdiness quotient (30.03) was also observed in seedlings raised in potting media composed of soil, sand, and farmyard manure (1:1:2). However, the maximum value of root shoot ratio (0.82) was recorded in seedlings raised in potting media composed of soil, sand, and farmyard manure (3:1:1) and maximum value of quality index was recorded in seedlings raised in potting media composed of soil, sand, and farmyard manure (1:1:3). The study recommended raising of seedlings of Prunus cerasoides in soil, sand and farm yard manure (1:1:2) for production of quality nursery stock.